Plastic contamination of composts derived from feedstocks with and without food waste - Hobson, Sarah A.; Porterfield, Katherine K.; Neher, Deborah A.; Scarborough, Matthew J.; Roy, Eric D. (Frontiers in Sustainable Food Systems, 2025)
Plastic has become a prominent material type used for numerous purposes since the 1950s and persists in waterbodies, sediments, and terrestrial soils worldwide. Through time, plastics break apart into smaller fragments that become dispersed throughout the environment. Organic waste derived soil amendments, such as compost, may serve as a transport vector for plastics into terrestrial soils. A Vermont-wide survey was conducted to provide a range of plastic abundance, mass, and types found in composts and contextualize future research on plastic effects. Twenty composts were analyzed including composts derived from feedstocks with both high (15% or more by volume) and low/no (5% or less by volume) food waste inclusion. Plastics were isolated in multiple size classes (> 5 mm, 1–5 mm, and 0.5–1 mm) with sieving, 30% hydrogen peroxide digestion, and microscopy. Fourier transform infrared (FTIR) spectrum similarity was also used to identify plastic polymers. Ranges of 0 to 1,201 plastic particles per dry kg of compost and 0 to 0.056% w/w plastic contamination on a dry mass basis were found across the composts. Plastic abundance was not a predictor of plastic mass. No statistical differences were found between the high and low/no food waste compost groups due to variability and relatively low sample sizes, although the five most contaminated composts (> 0.02% w/w) were all in the high food waste group. Methodological challenges and recommendations are also discussed, including emphasis on establishing confidence levels for putative microplastic confirmation under the uncertainty that is inherent to analyzing complex organic matrices using microscopy and FTIR.